SHARIA-BASED FINANCIAL STRATEGY: IMPLEMENTATION OF DEPOSITS WITH WADIAH CONTRACTS AT BMT NU - Romsi, Muhammad; Bari, Abdul (Ngejha, 2023)
This study aims to analyze the implementation of sharia-based financial strategies through deposit products with wadiah contracts at BMT NU, as well as evaluate the benefits and challenges faced in its implementation. This research method uses a qualitative approach with a case study on BMT NU, involving data collection through in-depth interviews with managers and customers, as well as document analysis related to wadiah deposit management policies and practices. Data analysis was carried out descriptively to identify factors that affect the effectiveness of the implementation of wadiah contracts and their impact on customer satisfaction. The results of the study show that the implementation of deposits with wadiah contracts at BMT NU offers various benefits, including legal certainty and protection of customer deposits. The wadiah contract allows financial institutions to maintain and manage customer funds with the principle of trust without the risk of usury. However, there are challenges such as the need to improve customer understanding of the principle of wadiah and manage expectations related to returns. This research provides insight into how sharia-based financial strategies, especially deposit products with wadiah contracts, can be effectively applied in sharia financial institutions. These findings are expected to help BMT NU and similar institutions in increasing the application of sharia products and maximizing their benefits for customers and the institution itself.